Does time spent in rehabilitation make a difference on activity limitation and impairment in people with stroke? - A Cochrane Review summary with commentary - Francesca Gimigliano (Medical Journals Sweden, 2022)
The aim of this commentary is to discuss from a rehabilitation perspective the Cochrane Review "The effect of time spent in rehabilitation on activity limitation and impairment after stroke"[1] by Clark B, Whitall J, Kwakkel G, Mehrholz J, Ewings S, Burridge J.,1 published by Cochrane Stroke Group. This Cochrane Corner is produced in agreement with the Journal of Rehabilitation Medicine by Cochrane Rehabilitation with views* of the review summary author in the "implications for practice" section.